2021
DOI: 10.1177/14644207211046122
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Al and Ti Transition Metals on the Wear Resistance of Ceramic Based CrN Coatings; Investigation under Ambient Air and Vacuum Conditions

Abstract: In the present study, CrN, CrAlN and CrAlTiN coatings were deposited using the cathodic arc evaporation technique. The structural investigations of these CrN based coatings were performed by scanning electron microscopy, energy dispersive spectroscopy, atomic force microscopy, X-ray diffractometer. The hardness and adhesion strength values of coatings were determined via Vickers type microhardness tester and progressive load scratch tester, respectively. The wear performance of samples was established at ambie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…The wear mechanism of the base material in ambient air is the consist of larger scratches, wrinkles, and delamination which indicated the adhesive wear characteristics (Figure 11(a)). 51 The scratches on the surface are formed as a result of the wear particles getting stuck between the mating surfaces due to the breaking of the micro weld connections formed in the said adhesive characteristic. 52 It is observed that the worn surface of the base material in SBF solution (Figure 11(b)) has smoother and shallower scratches compared to the ambient air.…”
Section: Resultsmentioning
confidence: 99%
“…The wear mechanism of the base material in ambient air is the consist of larger scratches, wrinkles, and delamination which indicated the adhesive wear characteristics (Figure 11(a)). 51 The scratches on the surface are formed as a result of the wear particles getting stuck between the mating surfaces due to the breaking of the micro weld connections formed in the said adhesive characteristic. 52 It is observed that the worn surface of the base material in SBF solution (Figure 11(b)) has smoother and shallower scratches compared to the ambient air.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this is that good adhesion properties between the coating and the substrate prevent coating spalling or buckling at shear stress formed during sliding friction. [20][21][22][23] The interlayer arrangement and number of layers have a significant impact on strength and friction behavior on multi-layer coatings. It was reported that adding Al to TiN and CrN increases the coating's mechanical properties, corrosion resistance, wear resistance, and melting point by increasing bond strength, lattice strain, and room temperature hardness.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the literature shows that coatings made of composite materials are more often used due to the fact that they often have better properties (antiabrasion, 11,12 tribological, 13,14 anticorrosion, 15,16 etc.) than coatings made of simple materials (made of one element or one single-phase two-component compound—e.g.…”
Section: Introductionmentioning
confidence: 99%